The Electrophysiology of Atrial Fibrillation: From Basic Mechanisms to Catheter Ablation - Panagiotis Ioannidis; Theodoros Zografos; Evangelia Christoforatou; Konstantinos Kouvelas; Andreas Tsoumeleas; Charalambos Vassilopoulos (Cardiology Research and Practice)
The electrophysiology of atrial fibrillation (AF) has always been a deep mystery in understanding this complex arrhythmia. The pathophysiological mechanisms of AF are complex and often remain unclear despite extensive research. Therefore, the implementation of basic science knowledge to clinical practice is challenging. After more than 20 years, pulmonary vein isolation (PVI) remains the cornerstone ablation strategy for maintaining the sinus rhythm (SR). However, there is no doubt that, in many cases, especially in persistent and long-standing persistent AF, PVI is not enough, and eventually, the restoration of SR occurs after additional intervention in the rest of the atrial myocardium. Substrate mapping is a modern challenge as it can reveal focal sources or rotational activities that may be responsible for maintaining AF. Whether these areas are actually the cause of the AF maintenance is unknown. If this really happens, then the targeted ablation may be the solution; otherwise, more rough techniques such as atrial compartmentalization may prove to be more effective. In this article, we attempt a broad review of the known pathophysiological mechanisms of AF, and we present the recent efforts of advanced technology initially to reveal the electrical impulse during AF and then to intervene effectively with ablation.